Crafting roles of clinical instructors in clinical placement in the department of clinical medicine in Kakamega county, Kenya - B. K. Wamalwa; J. N. Situma; S. N. Maragia (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Introduction: The roles of clinical instructors at the diploma level are lacking despite studies showing clinical instructors are an effective conduit for supporting the transfer of learning needed to address performance gaps in students. Clinical instructors increase the confidence of students in preparation for clinical practice and allow them to reflect on their professional development.Materials and Methods: A descriptive cross-sectional study was conducted on 400 clinical medicine students attending their clinical placements.Results: It was established that the core roles of the clinical instructors to clinical medicine students were mentorship to students in the clinical area, demonstrating of the clinical examination, follow-up, and supervising students.Conclusion: The study concluded that Mentors gave prominence to the needs of the students under their care and helped them manage nervousness during actual clinical practice.